The Tigriopus CURE – A Course-Based Undergraduate Research Experience with Concomitant Supplemental Instruction - Ginger R. Fisher (American Society for Microbiology, 2018)
Evidence indicates that students who participate in scientific research during their undergraduate experience are more likely to pursue careers in the STEM disciplines and to develop increased scientific reasoning and literacy skills. One avenue to increase student engagement in research is via their enrollment in course-based undergraduate research experiences (CUREs), where they are able to conduct authentic research as part of the laboratory curriculum. The information presented herein provides an example of a CURE which was developed and implemented in an introductory cell and molecular biology course at the University of Northern Colorado. In addition to describing the Tigriopus CURE curriculum itself, we also present evidence regarding the effectiveness of the CURE in promoting students’ development of confidence in science process skills, quantitative reasoning skills, and written communication skills. The curricular details of the Tigriopus CURE are provided in this article to provide instructors who are interested in CUREs the opportunity to implement this specific CURE in their own course.